Concept mapping effect on the cognitive learning outcomes of the concept of classification materials and their changes - Lu lu us Silvia; Elok Sudibyo; Ernita Vika Aulia (Jurnal Pijar Mipa, 2022)
This research aimed to describe the effectiveness of concept mapping in improving student cognitive learning outcomes in material classification materials and their changes implemented in the public Junior High Schools in Surabaya, Indonesia. The research design used one group pretest-posttest. This research involved 16 students from class VII. This research's data collection methods included observation, test, and questionnaire. The results showed that the implementation of learning got 88.15% and 97.36%, with excellent categories at the first and second meetings. The average N-Gain for all students is 0.5 in the medium category. The students' responses to learning got excellent results. Concept mapping with a cooperative learning type Student Teams Achievement Division STAD can improve student cognitive learning outcomes on classification materials and their changes.